Improvement of the separation evolution law and separation position determination method of mining overburden strata - Da, Yuxin; Ning, Zhiyuan; Huang, Zilong; Du, Qirui; Liu, Qi; Zhao, Jinhai; Li, Qinghai (Frontiers in Earth Science, 2023)
In view of the shortcomings of the traditional method of determining the separation position, according to the pressure balance arch in the overburden and the actual movement of the rock stratum, the concept of triangular separation domain is proposed, and the relationship between the range of triangular separation domain and mining distance and mining fracture angle is established. Considering the different length and curvature of each rock beam in the separation domain, the calculation method of rock load is modified. By analyzing the stress mode in the pressure arch of the separation zone, the mechanical model of the deflection calculation of each rock stratum is established, and the triangular separation zone is combined with the new mechanical model to establish a calculation model for the dynamic evolution analysis of the separation zone the calculation model of the composite beam in the separation zone.The model predicts the position of overburden separation by comparing the deflection between adjacent strata on the same horizontal contact surface, which makes the calculated separation position more accurate. The traditional method and the improved method are used to determine the separation position in a practical mining example.Field explorations confirmed that the results from the improved method described in this paper were more accurate.